Relative Effectiveness of Various Development Finance Flows: A Comparative Study - Kye Woo Lee; Minji Hong (KDI Journal of Economic Policy, 2018)
This paper aims to identify the most effective mode of development finance flows for the economic growth of middle-income developing and least developed countries, separately. It also attempts to confirm whether governance has any significant role in the causal relationship between development finance flows and economic growth. Policymakers in each developing country should select the most effective modality of development finance inflows among the different modalities (such as Official Development Assistance (ODA) grants, Official Development Assistance (ODA) loans, FDI, and international personal remittances) and expand it for their economic growth. Dynamic panel regression models were used on 48 least developed countries and 89 middle-income developing countries, respectively, during the Millennium Development Era: 2000-2015. The empirical analysis results show that ODA grants and remittances were most effective in promoting economic growth for least developed countries, while FDI was most effective for middle-income developing countries. These findings were not affected by the status of governance of the individual country.
Keywords: C36; F24; G15; O11; P45; 330; ODA Grants; ODA Loans; FDI; Remittances; Economic Growth; Least Developed Countries; Effectiveness; Middle-income Developing Countries